(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Fatma, Mallawa A, Najamuddin, Zainuddin M, Fachrie R. 2021. A study of brown-marbled grouper (Epinephelus fuscoguttatus) population dynamics in Takabonerate National Park Waters, South Sulawesi, Indonesia. Biodiversitas 22: 4298-4307. Understanding aspects of the population dynamics of groupers such as the brown-marbled grouper can provide valuable insights into how to manage grouper stocks effectively. Conducted from February 2020 to February 2021 in Takabonerate National Park waters, Selayar Islands District, South Sulawesi, Indonesia, this study sought to elucidate the size structure and cohorts, population growth rate, total mortality rate, fishing mortality rate, natural mortality rate, exploitation rate and yield per recruit (Y/R) of the brown-marbled grouper. Grouper samples were caught using several fishing gears (i.e., hand line fishing, spearfishing, and trapping) with a total catch of 1042 specimens. The sampled specimens exhibited significant size structure and were classified into five age-specific cohorts. The growth rate coefficient was 0.46/year, with the brown-marbled grouper population tending to exhibit slow growth (K < 0.5/year). The estimated asymptotic length was 109.0 cm. The fishing mortality was higher than the natural mortality, with an exploitation rate of 0.65, indicating that brown-marbled groupers in the waters of Takabonerate National Park have been subjected to extensive and intensive fishing, as also indicated by an estimated Y/R lower than the optimum Y/R rate.